Renal and vascular effects of the natriuretic peptide isolated from Crotalus durissus cascavella venom - Evangelista, Janaina S. A. M.; Martins, Alice M. C.; Nascimento, Nilberto R. F.; Sousa, Clauber M.; Alves, Renata S.; Toyama, Daniela O. [UNESP]; Toyama, Marcos H.; Evangelista, Joao Jose. F.; de Menezes, Dalgimar B.; Fonteles, Manasses C.; Moraes, Maria Elisabete A.; Monteiro, Helena S. A. (Pergamon-Elsevier B.V. Ltd, 2008)
Crotalus durissus cascavella is a snake that is usually found in the scrublands of northeast Brazil. The components of its venom may have effects on the vascular and renal systems. Recently, a new bradykinin inhibitory peptide has been identified in the venom of the Crotalinae family. The aim of the present study was to investigate the renal and vascular effects of the natriuretic peptide isolated from the venom of Crotalus durissus cascavella (NP2_Casca). The chromatographic profile showed the fractionation of substances identified as convulxin, gyroxin, crotoxin and crotamine, as well as fractions V and VI. The electrophoretic profile of fraction V consisted of several bands ranging from approximately 6 kDa to 13 kDa, while fraction VI showed only two main electrophoretic bands with molecular weights of approximately 6 and 14 kDa. Reverse-phase chromatography showed that NP2_Casca corresponds to about 18% of fraction VI and that this fraction is the main natriuretic peptide. NP2_Casca was compared to other natriuretic peptides from other sources of snake venom. All amino acid sequences that were compared showed a consensus region of XGCFGX, XLDRIX and XSGLGCX. The group treated with NP2-Casca showed an increase in perfusion pressure, renal vascular resistance, urinary flow and glomerular filtration rate. The percent of total and proximal tubular transport of sodium was reduced significantly after administration of the peptide. The mean arterial pressure showed a dose-dependent decrease after infusion of NP2_Casca, and an increase in nitrite production. In the aortic ring assay, NP2_Casca caused a relaxant effect in endothelium-intact thoracic aortic rings precontracted with phenylephrine in the presence and absence of isatin. NP2_Casca failed to relax the aortic rings precontracted with an isosmotic potassium Krebs-Henseleit solution. In conclusion, the natriuretic peptide isolated from Crotalus durissus cascavella venom produced renal and vascular effects. NP2_Casca reduced total and proximal sodium tubular transport, leading to an increase in sodium excretion, thereby demonstrating a diuretic action. A hypotensive effect was displayed in an arterial pressure assay, with an increase in nitrite production, suggesting a possible vasoactive action. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Crotalus durissus cascavella; Natriuretic peptide